Novel cerebrospinal fluid anti-central nervous system IgG antibodies can identify immunotherapy-responsive neuropsychiatric disorders - Preßler, Hannah; Bünger, Isabel; Prüss, Harald (Frontiers in Immunology, 2025)
BackgroundAutoantibodies (Abs) targeting the central nervous system (CNS) can cause various neuropsychiatric autoimmune diseases. The potential response to immunotherapy necessitates the continuous expansion of Ab testing strategies including non-antigen-specific screening assays. This study investigated whether tissue-based screening using unfixed murine CNS sections can help to identify patients with immunotherapy-responsive neuropsychiatric diseases after routine Ab panels yielded negative results.MethodsThis retrospective single-center study screened cerebrospinal fluid (CSF) of 279 patients for immunoglobulin G (IgG) anti-CNS Abs using unfixed mouse brain. Patients had a variety of neuropsychiatric conditions, in which an autoimmune contribution was considered. Previous testing for a panel of established autoantibodies using cell-based assays remained negative. Of 238 patients, paired serum samples were available.ResultsA subgroup of 55 patients (20%) showed novel anti-CNS autoantibody patterns in CSF, consisting of anti-myelin (n=13), anti-neuropil (n=14), anti-vessel (n=8), anti-tight junction (n=5), anti-cellular (n=8), and anti-astroglial (n=7) autoantibodies. Thirty-six patients (65%) fulfilled criteria for possible, probable, or definite autoimmune encephalitis or paraneoplastic neurological syndrome. Memory impairment (73%) and psychiatric abnormalities (64%) were the most frequent symptoms. Antibody subtypes were not significantly associated with clinical parameters at this sample size, however, there was a trend towards better response to immunotherapy with antibodies against myelin, neuropil, and neuronal cells, while patients with anti-vessel antibodies did not improve. CNS autoantibodies mainly disappeared parallel to clinical improvement. In 46% of treated patients, physicians would not have started immunotherapy without detection of anti-CNS autoantibodies, and the vast majority of patients stabilized or improved.ConclusionNovel CNS Abs were common in patients with suspected ‘seronegative’ autoimmune neuropsychiatric disorders. Detection facilitated identification of immunotherapy-responsive cases and enabled treatment initiation without increasing unnecessary treatments. Thus, tissue screening using unfixed mouse brain applied in patients with suspected neuropsychiatric autoimmune diseases parallel to established cell-based assays. Future studies should identify the underlying antigens, demonstrate the pathogenic role in animal models, and implement promising Abs into diagnostic routine panels.